PRE-DOMINANCE OF DELTA VARIANT AMONG UNVACCINATED AND VACCINATED INDIVIDUALS IN MULTAN REGION (Journal of Medical & Health Sciences Review, 2025)
The outbreak of pneumonia occurred in Wuhan, China, in December 2019, and a new virus entitled COVID-19, causing a severe pandemic worldwide, was found as the root cause. There was no effective treatment to control the infection so the epidemic was spreading day by day. To eradicate this global pandemic the SARS-CoV-2 vaccine is the only solution.  Globally on 17 July 2022, 567,348,657 cases were reported to WHO of COVID-19, including 6,387,224 deaths. In Pakistan on 17 July 2022, there were 1,543,741 confirmed cases with 30,424 deaths. The goal of this research was to find out, in retrospect, the viral load difference in vaccinated and unvaccinated individuals, and to determine the predominant variant in COVID-19-positive individuals in the Multan region. Our study was conducted in the molecular section of the Pathology department of Nishtar Medical University Multan in the time period from July 2021 to February 2022. Nasopharyngeal and oropharyngeal swabs were collected in viral transport media and immediately transported to the molecular laboratory, Pathology Department Nishtar Hospital Multan. Multan has 2.205 million mio. inhabitants  and is located in Punjab, Pakistan.  A qualitative Real-Time PCR was performed to detect the positivity and viral load by cycle threshold value. The variant was detected by whole genome sequencing. Results of our study showed that 69.80% of individuals were vaccinated and 30.20% were unvaccinated in 500 study subjects. Symptomatic individuals were 83.8% and 16.2% were asymptomatic. This study found no significant difference between vaccinated and unvaccinated COVID-19-positive patients. Of 86 sequenced study subjects, 94.19% showed the delta variant and 5.82% individuals were of non-delta variant. In both populations, the delta variation was the more common one. Irrespective of immunization eminence, age, sex and mean virus load, determined by cycle threshold value were different in substantial numbers of asymptomatic and symptomatic persons infested with SARS-Cov-2 throughout the delta peak in the current investigation. When compared to asymptomatic COVID-19-positive people, symptomatic COVID-19-positive individuals had a higher viral load.